Producción primaria en dos estuarios tropicales de la Costa Caribeña de Venezuela - Rodríguez, G. L. (1989)
Of two estuaries studied by means oC the C14 method, the Tacarigua lagoon showed the highest values of production, generally above 30 mgC/m3/hr, with a peak of 187.76 mgC/m3/hr. In Maracaibo the highest recorded value was 46.33 mgC/m3/hr. but with an irregular vertical distribution attributable to strong vertical mixing. A marine locality on the coast showed values considerably lower (2-3 mgC/m3/hr)